A Janus evaporator based on Donnan effect for efficient solar thermal desalination - Hai-Tao Ren; Hong-Bei He; Qing-Kai Zhu; Ting-Ting Li; Ching-Wen Lou; Jia-Horng Lin (Desalination, 2024)

Investigation of verapamil-induced cardiorenal dysfunction and compensatory ion regulation in zebrafish embryos - Jiun-Lin Horng; Bu-Yuan Hsiao; Wen-Ting Lin; Tzu-Ting Lin; Ching-Yen Chang; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Mitigating thermal burden and enhancing minor phase emission energy transfer in perovskite by introducing dopamine-mediated silver nanoparticles - Zhen-Li Yan; Jhih-Yuan Chang; Chieh Tsao; Meng-Xiu Fang; Bi-Hsuan Lin; Jia-Hau Tsai; Mei-Hsin Chen; Ru-Jong Jeng; Chi-Ching Kuo (Chemical Engineering Journal, 2024)

High efficiency in blue TADF OLED using favorable horizontal oriented host - Yi-Zhen Li; Hsuan-Chi Liang; Chia-Hsun Chen; Ching-Huang Chiu; Lian-Chun Huang; Yi-Ting Lee; Yi-Chung Dzeng; Chi Chen; Bo-Yen Lin; Jiun-Haw Lee; Tien-Lung Chiu; Man-kit Leung (Chemical Engineering Journal, 2024)

Development of Quantitative Norms for Normal Lung Uptake Based on Three-Dimensional Gallium-67 Single Photon Emission Computed Tomography/Computed Tomography - Tzyy-Ling Chuang; Wei-Lin Li; Yu-Ching Hs; Jyh-Cheng Chen; Yuh-Feng Wang (Journal of Medical and Biological Engineering, 2024)
Purpose Gallium-67 (Ga-67) lung scans assess alveolitis and interstitial lung disease, with Ga-67 accumulation correlating with inflammation intensity as seen in lung biopsy sections. Both semi-quantitative and quantitative methods have been used, with the latter providing an inflammatory activity index linked to lung lavage and histopathological scores. However, differing reference points result in varying outcomes. This study aimed to establish standard Ga-67 index parameters using semi-quantitative analysis and a linear regression model based on planar and SPECT/CT images. Methods Twenty subjects without lung disease received a 5–6 mCi Ga-67 injection via the ankle. Both planar and SPECT/CT images were analyzed, with semi-quantitative values assessed using GraphPad Prism 9.5.1. Results Compared to planar images, SPECT/CT acquisitions for the lung-to-arm uptake ratio proved the most reliable indicator for assessing lung inflammation. Increased lung Ga-67 uptake was defined as greater than 2 standard deviations from the average Ga-67 uptake for healthy subjects. The normal range was 0.065 ± 0.049 for the right side and 0.076 ± 0.070 for the left side. Conclusion Lung-to-arm ratios in SPECT/CT images are more accurate than those in planar images. This method should be adopted as a standard clinical practice, providing more reliable diagnostic information and improving patient management. Future studies should compare patients without lung disease to those with lung disease to determine the diagnostic benefit of these norms.

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Energy transition: Cap-and-trade and carbon capture and storage for achieving net-zero emissions with sustainable insurance - Shi Chen; Yuqi Li; Jyh-Horng Lin; Ching-Hui Chang (Journal of Environmental Management, 2024)

Kaguacidine A: a novel spirohydantoin-containing cucurbitane glycoside from vines of Momordica charantia L. - Hung-Tse Huang; I-Wen Lo; Yu-Chi Lin; Liao Geng-You; Yun-Sheng Lin; Li-Jie Zhang; Tsung-Lin Li; Chia-Ching Liaw; Yao-Haur Kuo (Natural Product Research, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

An Automatic Approach of Video-Based Landmark Detection and Movement Analysis for Assessing Symptoms of Bradykinesia in Parkinson’s Disease - Ching-Fang Chien; Chen-Sen Ouyang; Yi-Hung Chiu; Lung-Chang Lin; Rei-Cheng Yang; Yang-Pei Chang; San-Yuan Wang; Li-Min Liou (Journal of Medical and Biological Engineering, 2024)

Meteotsunamis in the Tamsui River estuary, Taiwan - Li-Ching Lin; Wen-Cheng Liu; Chin H. Wu (Estuarine, Coastal and Shelf Science, 2024)

Assessing cardiovascular toxicity in zebrafish embryos exposed to copper nanoparticles - Bu-Yuan Hsiao; Jiun-Lin Horng; Ching-Hua Yu; Wen-Ting Lin; Yu-Han Wang; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Rosette-like (Ni,Co)Se2@Nb2CTx MXene heterostructure with abundant Se vacancies for high-performance flexible supercapacitor electrodes - Baolei Shen; Xianjin Hu; Hai-Tao Ren; Hao-Kai Peng; Bing-Chiuan Shiu; Jia-Horng Lin; Ching-Wen Lou; Ting-Ting Li (Chemical Engineering Journal, 2024)

Photothermal-driven pH-responsive fiber composite membrane for oil-wastewater purification - Shuxia Li; Jia-Horng Lin; Hai-Tao Ren; Bing-Chiuan Shiu; Fei Sun; Ching-Wen Lou; Ting-Ting Li (Journal of Environmental Chemical Engineering, 2024)

A 16-year meteotsunami climatology in the coastal areas of southern Asia-Pacific Ocean - Li-Ching Lin; Wen-Cheng Liu; Chin H. Wu (Frontiers in Marine Science, 2024)
This study presents the meteotsunami behavior in response to different storm types in the coasts of southern Asia-Pacific Ocean from 16 years water level records. Through the size- frequency analysis, the dangerous meteotsunami, wave height exceeding 0.3 m, can occur up to 44 events per year. Notably, during the extreme waves of the 2007 event, wave heights reached approximately 0.9-1.5 m in the Taiwan Strait and the western coastal areas of Taiwan. We have classified storms into six types by radar reflectivity images and satellite-derived precipitation. Findings indicate that predicted wave heights caused by bows and typhoons could reach hazardous magnitude of exceeding 2 m in a 100-yr interval. Spatial and temporal analysis reveals that meteotsunami occurrences are most frequent in the western regions during the winter to early spring months (December to April). Of all meteotsunami occurrences, cluster storms are identified as the most prevalent atmospheric forcing, accounting for 60% of meteostunamis. Typhoons have a 20% association with meteotsunamis along the east coasts of Taiwan during late summer to autumn. On the east coasts, typhoon type-induced events may be attributed to the combination effect of meteotsunamis and infra-gravity waves. Overall, this study provides the first comprehensive examination of meteotsunami-storm characteristics and their associated hazard risks in the coastal areas of the southern Asia-Pacific Ocean.

Microplastics elicit an immune-agitative state in coral - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li; Fu-Wen Kuo (Science of The Total Environment, 2024)